2000
DOI: 10.1056/nejm200006153422403
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Left Ventricular Hypertrophy and Risk of Sudden Death in Hypertrophic Cardiomyopathy

Abstract: In hypertrophic cardiomyopathy, the magnitude of hypertrophy is directly related to the risk of sudden death and is a strong and independent predictor of prognosis. Young patients with extreme hypertrophy, even those with few or no symptoms, appear to be at substantial long-term risk and deserve consideration for interventions to prevent sudden death. The majority of patients with mild hypertrophy are at low risk and can be reassured regarding their prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
561
3
36

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 999 publications
(626 citation statements)
references
References 29 publications
13
561
3
36
Order By: Relevance
“…27,28 Males and females differ in their presentation of HCM, with cohorts usually having a predominance of males. [29][30][31] In our study, an effect of gender on age at onset in the relatives was observed: men were affected at younger age than women. This may be explained by a protective role of estrogens in the hypertrophic response and the evidence that exposure of cardiac myocytes to androgen results in hypertrophy.…”
Section: Discussionsupporting
confidence: 53%
“…27,28 Males and females differ in their presentation of HCM, with cohorts usually having a predominance of males. [29][30][31] In our study, an effect of gender on age at onset in the relatives was observed: men were affected at younger age than women. This may be explained by a protective role of estrogens in the hypertrophic response and the evidence that exposure of cardiac myocytes to androgen results in hypertrophy.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, a subgroup of younger patients with HOCM (with a thicker basal septum at baseline) requires interventional therapy decades sooner as the result of intrinsic myocardial processes associated with a more "malignant" form of HCM. 25 The large and very compelling study published by Spirito et al 26 involved 480 patients with HCM, 43 of whom had marked hypertrophy. Mortality was 18.2% in the marked hypertrophy cohort during an average 7-year follow-up, which was significantly more than in the group with less hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Elimination or reduction of LVOT obstruction is associated with improved functional status and less symptoms. Currently, the primary options to achieve this aim include myectomy 4 -6 and septal alcohol ablation.…”
Section: Eft Ventricular Outflow Tract (Lvot) Obstruction Ismentioning
confidence: 99%